Interactive learning: advantages and disadvantages - Kustovska, O.; Svidenyuk, A. (Land Management, Cadastre and Land Monitoring, 2017)
In the article the use of interactive technologies in the educational process of the university,allowing students to develop innovative thinking, away from stereotypes, developimagination, communication skills and expertise, intellectual, emotional, motivational andother areas of personality. Implementing the principles of technological learning, interactiveeducational technology and provides interactive computer learning tools, and interactivityof educational process when the basic conceptual provisions defined training based oninteractive communication.Key words: interactive learning technology, teacher, students, innovative thinking,communication skills.